If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 3x + 1 + -1x = -6 + 3x + 7 + -2x Reorder the terms: 5 + 1 + 3x + -1x = -6 + 3x + 7 + -2x Combine like terms: 5 + 1 = 6 6 + 3x + -1x = -6 + 3x + 7 + -2x Combine like terms: 3x + -1x = 2x 6 + 2x = -6 + 3x + 7 + -2x Reorder the terms: 6 + 2x = -6 + 7 + 3x + -2x Combine like terms: -6 + 7 = 1 6 + 2x = 1 + 3x + -2x Combine like terms: 3x + -2x = 1x 6 + 2x = 1 + 1x Solving 6 + 2x = 1 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + 2x + -1x = 1 + 1x + -1x Combine like terms: 2x + -1x = 1x 6 + 1x = 1 + 1x + -1x Combine like terms: 1x + -1x = 0 6 + 1x = 1 + 0 6 + 1x = 1 Add '-6' to each side of the equation. 6 + -6 + 1x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = 1 + -6 1x = 1 + -6 Combine like terms: 1 + -6 = -5 1x = -5 Divide each side by '1'. x = -5 Simplifying x = -5
| 8y-2=18 | | 17-(4m+6)=5+4m-18 | | -12-2x=8(8-5x) | | 5xy+10=25 | | 4x+144+2x+156=180 | | 15-(-6)=x | | 2=b+9/8 | | 1/2a7 | | -18=x+7+4x | | 10+x/9=1 | | 2x+42-5x=1-9x+5 | | 4=n/3-1 | | 4x+48=7x+36 | | -9m=-63 | | 5m+8=9m-4 | | 15k^2+6k= | | -14-n=-7 | | 2a-7=-7 | | x^2-8xy-9y^2= | | a^2-4ac+ab-4bc= | | 720=(2x-6)(x+6) | | (sin(5x))/x | | -40=r-19 | | 27-b=16 | | 27x-8.5x+27x-4.6=3-.5 | | 3x^2+15= | | 16=4n-18 | | (3x^3+4x-1)(x^2+1)= | | 24a^2b^2-18ab= | | -2+1/3a=-9 | | -2u-3=11 | | y^3-2y^2=0 |